Death Games and the Persistence of Memory: J. G. Ballard’s World War II Fictions - Pedro Groppo (Ilha do Desterro)
This article is a discussion of J. G. Ballard’s (semi-)autobiographical war narratives, with a focus on the different textual strategies and processes of signification Ballard employs from his avant-garde novel The Atrocity Exhibition (1970) to the feverish fictional account of his time in World War II China in “The Dead Time” (1977) and Empire of the Sun (1984) to his more reflective autobiographical texts The Kindness of Women (1990) and Miracles of Life (2008). Ballard’s obsessive repetition of many of the same images and attest to a problematics of representation of the traumatic event, and ultimately they represent a complex and rich work of fabulation that escape categorizations of fiction and autobiography.